2017
DOI: 10.3390/geosciences7040125
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Analysis of Land Use and Land Cover Transitions from 1986–2014 in a Peri-Urban Ghana

Abstract: Abstract:Recently, peri-urbanisation has led to the transformation of the rural landscape, changing rural land uses into peri-urban land uses, under varying driving factors. This paper analyzes the dynamic transitions among identified land use and land cover (LULC) types in the Bosomtwe district of Ghana, from 1986 to 2014. An integrated approach of geo-information tools of satellite remote sensing in Earth Resource Data Analysis System (ERDAS) Imagine 13 and ArcMap 10.2 Geographic Information System (GIS), wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The population in many urban areas in sub-Saharan Africa has grown significantly due to rural-urban migration as a result of lack of employment opportunities and social amenities in the rural areas. Other studies have also identified urbanisation to be the key cause of land cover changes within forest reserves in Ghana [36,37]. In Namibia and Kenya, investigations have identified agricultural expansion, population growth increase and illegal logging as the key drivers of land use and land cover changes, with serious debilitating effects on peoples' livelihood activities [38].…”
Section: Discussionmentioning
confidence: 99%
“…The population in many urban areas in sub-Saharan Africa has grown significantly due to rural-urban migration as a result of lack of employment opportunities and social amenities in the rural areas. Other studies have also identified urbanisation to be the key cause of land cover changes within forest reserves in Ghana [36,37]. In Namibia and Kenya, investigations have identified agricultural expansion, population growth increase and illegal logging as the key drivers of land use and land cover changes, with serious debilitating effects on peoples' livelihood activities [38].…”
Section: Discussionmentioning
confidence: 99%
“…Urbanization brings a range of environmental challenges for the local, regional, and wider environment as a direct result of the changes it brings to local hydrologic regimes [1][2][3][4]. The loss of pervious surfaces reduces infiltration into soils, while the introduction of artificial drainage replaces natural pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Key informants established that it has led to declining or failure of crop production, soil infertility, change in rainfall pattern, overdependence and unsustainable extraction of natural resources which causes serious environmental problems. Overdependence and unsustainable use of wetland resources without alternative economic livelihood options have led to soil erosion, biodiversity loss, natural-resource depletion, water, and air pollution, disintegration, and wetland degradation (Munthali et al, 2019;Appiah et al, 2017). Similarly, the wetland is not demarcated, this situation is similar to several wetlands in tropical Africa.…”
Section: Population Growth Socioeconomic Characteristics and Their Imentioning
confidence: 99%